Analyzing Tiktok’s Role in Shaping Health Behaviour - Anak Jeffry Douglas, Irvina Joan; Mohamad Ridzwan, Nurlisa; Binti Mohammad Bakhtiar, Nurul ‘Atiqah; Binti Nasrin, Nurul Atiqah; Jamri, Mohamad Hafifi; Zul Chairiyah, Sri; Djuyandi, Yusa (PT. Data Jaringan Visual Indonesia (Djava), 2025)
This study employs a descriptive survey design to comprehensively assess consumer behaviours towards health products promoted on TikTok, targeting Malaysian citizens aged 18 and above. Despite the platform's increasing popularity for health product advertisements, scepticism persists regarding the efficacy of products endorsed by TikTok influencers. Findings reveal a positive response towards TikTok's influence on purchasing behaviour, with users acknowledging the need to verify health claims before making purchases. While there's a slight preference for health products endorsed by influencers, informed decision-making is emphasised. Positive feedback from TikTok users influences others' decisions to try health products, but concerns arise over potential misinformation dissemination and discrepancies between healthcare provider recommendations and patient preferences. Users prioritise influencer credibility and medical expertise, although not all actively seek health-related content. The study sheds light on TikTok's role in shaping consumer perceptions and behaviours, guided by the Transactionality Paradigm Theory. Future research could delve into long-term effects of TikTok endorsements, strategies to mitigate misinformation, and regulatory oversight to enhance consumer trust in health-related advertisements on social media platforms.